Kesehatan jiwa dalam keluarga, sekolah dan masyarakat - Musthafa Famhi (Bulan Bintang, 1977)
tr, jil.1=c.1-9; Jil. 2=c.1-5; Jil. 3=c.1-4/ir jil.2,c.6 /ir,jil.1,c.10/ast jil.1 =c.11/TR, JIL.1=C.12-13; JIL.2=C.7-9; JIL.3-=C.5-6/stoc2, jil.1=c.1-13, jil.2=c.1-9, jil.3=c.1-6.